Inhibition of Herpes Simplex Virus Type 2 Replication by Thymidine - Cohen, Gary H. (1974)
Replication of herpes simplex virus type 2 (HSV-2) was impeded in KB cells which were blocked in their capacity to synthesize DNA by 2 mM thymidine (TdR). The degree of inhibition was dependent upon the concentration of TdR. In marked contrast, HSV-1 is able to replicate under these conditions. The failure of HSV-2 to replicate is probably due to the inhibition of viral DNA synthesis; there was a marked reduction in the rate of DNA synthesis as well as the total amount of HSV-2 DNA made in the presence of 2 mM TdR. We postulated that the effect of TdR on viral replication occurs at the level of ribonucleotide reductase in a manner similar to KB cells. However, unlike KB cells, an altered ribonucleotide reductase activity, highly resistant to thymidine triphosphate inhibition, was found in extracts of HSV-2-infected KB cells. This activity was present in HSV-2-infected cells incubated in the presence or absence of TdR. Ribonucleotide reductase activity in extracts of HSV-1-infected KB cells showed a similar resistance to thymidine triphosphate inhibition. These results suggest that the effect of TdR on HSV-2 replication occurs at a stage of DNA synthesis other than reduction of cytidine nucleotides to deoxycytidine nucleotides.